Effect of organic calcium salts–inulin systems on hydration and thermal properties of wheat flour - Salinas, Maria Victoria (2013)
The aim of this work was to study the effect of calcium acid salts–inulin systems on hydration and thermal properties of wheat flour dough. Wheat flour was enriched with calcium lactate (CaLa2) or calcium citrate (Ca3Ci2) (1080–2520 ppm Ca) and inulin (In) (1%–13%, w/w flour basis). Water absorption (Wabs), moisture content (Mcont), water activity (aw) and relaxation time (λ) of dough were analyzed. Pasting properties during heating–cooling process were studied: peak viscosity (PV), breakdown (BD), final viscosity (FV) and setback 1(SB1) were determined. Temperatures (TpI, TpII) and enthalpy (ΔHgel) of gelatinization of dough were analyzed by DSC. Samples with Ca and In presented lower Wabs than control sample with an In2 dependence, with slight difference between both surface responses. More time for dough development (td) was necessary with Ca3Ci2 than with CaLa2, being td independent of calcium content at In level (≥6.5%). Dough with Ca3Ci2 was more stable with less degree of softening than CaLa2-dough, due to the protein stabilizing effect of citrate ion (Hofmeister series) with a maximum at 6.5% In. Mcont and λ decreased with the increase of In, independently of calcium. Hydration properties directly influenced pasting parameters. The increase in In content decreased viscosity (PV, FV) without affecting BD. SB1 behavior suggests the formation of pastes with low and high stability with CaLa2 and Ca3Ci2, respectively. Gelatinization degree decreased (40%) and retarded (ΔT=10 °C) at high levels of both ingredients. CaLa2 had more influence in hydration and thermal properties of wheat flour–inulin blends, enhancing a high degree of inhibition of gelatinization and leading to pastes with low viscosity after cooling. This behavior was influenced by the presence of inulin.